PHYTOCHEMICAL AND ANTIBACTERIAL ACTIVITIES OF A. CHEVALIERI HAMS (FABACEAE) STEM - Namadina, Murtala M.; Idris, A. M.; Sunusi, U.; Abdulrazak, M. H.; Musa, F. M.; Olaogun, O. N.; Balarabe, S.; Yakubu, N.; Sani, M. H.; Ali, Z. A.; Nuhu, Y.; Makin, T. Y.; et al. (FUDMA JOURNAL OF SCIENCES, 2021)
Albizia chevalieri Hams (Mimosaceae/Fabaceae), mostly found in the Northern Sahel Savannah region of Nigeria as well as in NigÃ©r and Senegal is a tree of the acacia type with a long list of folklore therapeutic claims that include its use as purgative, taenicidal, cough remedy, dysentery, cancer, diabetes mellitus, tuberculosis and snake bite remedy. However, many bacterial species have been reported to develop resistance to antibiotics commonly prescribed for dental infections. Therefore, the need to search for natural products for remedy to this problem cannot be overemphasized. The stem was collected, dried and powdered. The powder was thereafter extracted with distilled water and subsequently with methanol. Phytochemical screening was carried out using standard methods. Agar well diffusion, agar dilution and spread plate methods were employed to determine the zone of inhibition, Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and rate of killing respectively. Phytochemical screening of methanol and aqueous extracts of Albizia chevalieri stem revealed the presence of phenol, alkaloid, saponins, tannins, steroids, triterpenes, flavonoids and carbohydrate as secondary metabolites. The two extracts showed broad spectrum of activity but the aqueous extract had larger zones of inhibition of 32 mm against S. mutans while methanol extract had higher zone of inhibition on S. aureus (24 mm). Low MIC and MBC values ranging from 6.25 mg/ml and 12.5 mg/ml respectively. The results obtained also provided scientific evidence for the use of A. chevalieri in folklore medicine in the treatment of tooth infections.